Cold responsive gene transcription becomes more complex. (August 2015) - Zhao, Chunzhao; Lang, Zhaobo; Zhu, Jian-Kang
<x xml:space="preserve">Abstract</x> CBF transcription factors, which play important roles in cold acclimation, regulate the expression of approximately 170 cold-responsive genes, termed the CBF regulon. Recent work by Park et al. showed that CBF regulon genes and other cold-responsive genes are regulated by a complex network that involves many early cold-induced transcription factors.